Rates of Filtration and Ingestion of a Microalga by Philodina roseola (Rotifera: Bdelloidea) (2016)
Rotifers play an important role in biogeochemical cycles and organic productivity of freshwater ecosystems due to their high metabolic rates. Information on filter feeding, their main process of energy acquisition, are relevant and still scarce for tropical regions. The rotifers of the class Bdelloidea feed by filtration or scraping consuming small food items, such as bacteria, algae, yeasts or particulate organic matter. We know little of their role in the trophic dynamics in the habitats they occupy and so the aim of this study was to quantify laboratory filtration and ingestion rates of the rotifer Philodina roseola, fed with Raphidocelis subcapitata. The experiment consisted of 10 adult exposure treatment at five concentrations approximately in the range between 104 and 107 cells mL-1, at the temperature of 25 ± 1 °C. The experiments lasted one hour and initial and final concentrations of the algal suspensions were determined by counting the number of cells in a Neubauer chamber. There were no significant differences between the initial and final concentrations of cells in the control group indicating that algal growth did not occur. Philodina roseola filtration rates varied between 0.09 and 0.25 mL ind-1 h-1. Given that filtration is the main process of energy acquisition by Philodina roseola, as well as for most other rotifers, and that it comprises important issues related to trophic dynamics of aquatic ecosystems, additional experimental information is especially important and need to be extended to other types of food and combinations of experimental conditions.